A putative greigite‐type magnetosome gene cluster from the candidate phylum Latescibacteria. Issue 2 (17th December 2014) - Lin, Wei; Pan, Yongxin
Summary The intracellular biomineralization of magnetite and/or greigite magnetosomes in magnetotactic bacteria (MTB) is strictly controlled by a group of conserved genes, termed magnetosome genes, which are organized as clusters (or islands) in MTB genomes. So far, all reported MTB are affiliated within the Proteobacteria phylum, the Nitrospirae phylum and the candidate division OP3. Here, we report the discovery of a putative magnetosome gene cluster structure from the draft genome of an uncultivated bacterium belonging to the candidate phylum Latescibacteria (formerly candidate division WS3) recently recovered by Rinke and colleagues, which contains 10 genes with homology to magnetosome mam genes of magnetotactic Proteobacteria and Nitrospirae. Moreover, these genes are phylogenetically closely related to greigite‐type magnetosome genes that were only found from the Deltaproteobacteria MTB before, suggesting that the greigite genes may originate earlier than previously imagined. These findings indicate that some members of Latescibacteria may be capable of forming greigite magnetosomes, and thus may play previously unrecognized roles in environmental iron and sulfur cycles. The conserved genomic structure of magnetosome gene cluster in Latescibacteria phylum supports the hypothesis of horizontal transfer of these genes among distantly related bacterial groups in nature.